2018
DOI: 10.1186/s12943-018-0899-5
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Tumour-originated exosomal miR-155 triggers cancer-associated cachexia to promote tumour progression

Abstract: Emerging evidence supports the pivotal roles of cancer-associated cachexia in breast cancer progression. However, the mediators and mechanisms that mediate cancer-induced cachexia remain unclear. Here, we show that breast cancer-derived exosomes alter adipocytes and muscle cells in terms of increased catabolism characterized by the release of metabolites. Likewise, tumour cells cocultivated with mature adipocytes or C2C12 exhibit an aggressive phenotype through inducing epithelial-mesenchymal transition. Mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
115
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 101 publications
(119 citation statements)
references
References 9 publications
4
115
0
Order By: Relevance
“…Numerous studies have revealed that miRNA is intimately related to tumor initiation and progression. 38,39 Present works have confirmed that miR-31 is downregulated in liver cancer and involved in liver cancer cell apoptosis, migration impairment, and proliferation delay. 10,40 But the underlying mechanisms remain unclear.…”
Section: Discussionmentioning
confidence: 84%
“…Numerous studies have revealed that miRNA is intimately related to tumor initiation and progression. 38,39 Present works have confirmed that miR-31 is downregulated in liver cancer and involved in liver cancer cell apoptosis, migration impairment, and proliferation delay. 10,40 But the underlying mechanisms remain unclear.…”
Section: Discussionmentioning
confidence: 84%
“…In addition to CAFs and MSCs, other noncancerous cells are influenced by tumor-derived EV-RNAs to disrupt their normal phenotypes. EV-miR-155 from BC cells could promote brown differentiation and catabolism of adipocytes by targeting PPARγ [168]. Tumorderived EV-miR-21 promotes apoptosis of skeletal muscle cells by activating TLR7 [169].…”
Section: Regulation Of Malignant Phenotypes Of Cancer Cells By Tumor mentioning
confidence: 99%
“…Yet, mir-155-5p secreted by human breast cancer cells was proven to promote WAT browning and increased BAT thermogenesis but not lean mass loss. This was due to the targeting of peroxisome proliferatoractivated receptor gamma (PPARγ), a well-known regulator of glucose metabolism and fatty acid storage (69).…”
Section: Micrornasmentioning
confidence: 99%